Learn public speaking [videorecording (DVD)] (Cerebellum Corp., 2002)
"The Standard Deviants will help you overcome your fear of public speaking and help you deliver your message with style and flair! Using proven attention-getters, illustrations and delivery suggestions, Public Speaking will help you organize your thoughts and present them in a clear and persuasive manner"--Publisher Web site.